Evaluación de la responsabilidad social empresarial y su contribución a la situación económica del hotel Oro Verde de Manta - Navarrete Muñoz, Karina Elizabeth (2022)
The main objective of this research was to evaluate the Corporate Social Responsibility and its economic contribution of the Oro Verde hotel in Manta. It was a descriptive, bibliographic and field investigation, in which analytical, deductive and accounting methods were incorporated; accompanied by the Delphi methodology for the validation of the survey instrument, likewise, the Likert scale valued in a range of 1 to 5 was used. The research was carried out in 3 phases; The first one consisted of determining the level of compliance with the social, economic and environmental dimensions, then measuring the impact of CSR on the financial situation and, as a third phase, proposing an action plan to improve the Oro Verde hotel in Manta. Before the execution of the same, the results indicated that the establishment puts CSR into practice at a level of voluntary compliance and by regulations, which follows that they include it mostly in their business activities. It was verified with the financial tools that CSR contributes economically in the reduction of costs and expenses that the establishment emanates; Finally, in the weakest points of CSR compliance, an action plan was proposed with the help of the 5w+1h matrix to counteract said problems that may affect the hotel company. Finally, the interest in obtaining a better economic situation has awakened in companies the initiative to carry out socially responsible actions.